SMART WATER BOTTLE - Nagendran, Srikanth (IRC, 2020)
Final Year Project (FYP) is an initiative conducted by the universities that every university student undergoes before graduating. I was aware of the current global situation whereby global warming is on the rise and people are too focused in the industrial world and neglects to drink enough water to stay healthy. Therefore, I took this opportunity to do my research on dehydration and come up with a project on it. This proposal is written for the development of Smart water bottle, my final year project for Universiti Teknologi Petronas (UTP). Effective and proper methodologies are being use which are preliminary studies and system development to complete this project. To conduct the preliminary studies, literature review of the project and surveying the general public were done. For system development, I decided to use the Iterative methodology. Thus, I have done a research will focus on dehydration and how to come up with a gadget to overcome it.